The Effect of work Discipline and Work Motivation on Employee Performance - Susamai, Ahmad Akbar; Cay, Sam (Journal of Investment Development, Economics and Accounting, 2025)
The aim of this research is to overcome the influence of work discipline and work motivation on employee performance at PT Simultaneous South Tangerang City Investment Development. The method used is a quantitative method. The population was 62 respondents using the saturated side technique method with a sample of 62 respondents. Data analysis uses research instrument tests, classical assumption tests, descriptive tests, quantitative tests and hypothesis tests. The results of the calculated t value > t table or (7.082> 20030). this shows that there is a partial positive and significant influence between work disciplines on employee performance at PT. South Tangerang City Investment Development. The results of the calculated t value > t table or (3,451> 2.0030), this shows that there is a partial positive and significant influence between work motivation on employee performance at PT. South Tangerang City Investment Development. The calculated F value > F table or (5.901 > 3.153), this shows that there is a positive and significant influence simultaneously between the variables of work discipline and work motivation on employee performance at PT South Tangerang City Investment Development.